Relationship of vitamin D, BMI and BMD in age and gender linked population - Ganguli, Ritwik; Pahari, Priyanka (International Journal of Research in Orthopaedics, 2018)
Background: Vitamin D insufficiency prevalence has been related to low bone mineral density (BMD). However, controversial results have been reported for the relationship between serum 25-hydroxyvitamin D [25(OH)D] levels and BMD. This study was done to investigate whether serum 25(OH)D levels were associated with BMD in different age group and sex link population. Methods: This study involved, aged 40-70 yr, who is consecutively selected from KPCMCH, BMD camp. BMD was measured at the lumbar spine and femoral neck. The correlation between serum 25(OH)D levels and BMD was investigated. Results: Vitamin D levels for healthy and patients individuals at hospital. The age of 40 healthy subjects ranged from 40 to 70 years with the average of 55.30±10.30 years and body mass index (BMI) ranged from 18 to 37 kg/m2, with the of average of 28.90±5.20 kg/m2. Comparison between healthy and patients based on BMI and vitamin D level for the overweight BMI healthy individuals was 29.78±9.40 ng/ml, and that of hyperlipidemic patients was 24.47±8.78 ng/ml. Conclusions: In this study, there is significant different between healthy and patients group in vitamin D3level.BMD significantly decreased in patients group more elderly.